Henoch-Schönlein Purpura with Gastrointestinal Tract Involvement and Nephritis in Children in Limited Healthcare Settings - Sari, Dewi Wulan; Wahyuni, Ike Dwi (Transpublika Publisher, 2026)
Henoch-Schönlein Purpura (HSP), or IgA vasculitis, is the most common systemic vasculitis in children, characterized by a clinical tetrad of palpable purpura, arthritis/arthralgia, abdominal pain, and renal involvement. Gastrointestinal manifestations may mimic surgical acute abdomen, while nephritis determines the long-term prognosis. This case report aims to present the management of HSP with multi-organ involvement in a limited-resource setting. An 8-year-old girl presented with nausea, vomiting, and severe abdominal pain, preceded by the appearance of a reddish rash on the extremities and buttocks one week prior. Physical examination revealed diffuse palpable purpura and epigastric tenderness. Investigations showed leukocytosis, microscopic hematuria, and mild proteinuria. Abdominal ultrasound revealed positive sonographic tenderness at McBurney’s point without signs of acute appendicitis or intussusception. The patient was diagnosed with HSP with gastrointestinal involvement and nephritis. The patient was treated conservatively with intravenous hydration, antibiotics, gastric mucosa protectors, and systemic corticosteroids. Significant clinical improvement in abdominal pain and skin rash was achieved following corticosteroid administration, and the patient was discharged with a prednisone tapering regimen. Early diagnosis of HSP is crucial to avoid unnecessary surgical intervention in patients with severe abdominal pain. Corticosteroids are effective in relieving acute gastrointestinal symptoms. Long-term monitoring of renal function is mandatory given the risk of chronic kidney disease progression, even in cases with mild initial symptoms.